HIV-1 gp120 Impairs Spatial Memory Through Cyclic AMP Response Element-Binding Protein - Shrestha, Jenny; Santerre, Maryline; Allen, Charles N. S.; Arjona, Sterling P.; Merali, Carmen; Mukerjee, Ruma; Chitrala, Kumaraswamy Naidu; Park, Jin; Bagashev, Asen; Bui, Viet; Eugenin, Eliseo A.; Merali, Salim; et al. (Frontiers in Aging Neuroscience, 2022)
HIV-associated neurocognitive disorders (HAND) remain an unsolved problem that persists despite the use of antiretroviral therapy. We have obtained data showing that HIV-gp120 protein contributes to neurodegeneration through metabolic reprogramming. This led to decreased ATP levels, lower mitochondrial DNA copy numbers, and loss of mitochondria cristae, all-important for mitochondrial biogenesis. gp120 protein also disrupted mitochondrial movement and synaptic plasticity. Searching for the mechanisms involved, we found that gp120 alters the cyclic AMP response element-binding protein (CREB) phosphorylation on serine residue 133 necessary for its function as a transcription factor. Since CREB regulates the promoters of PGC1 and BDNF genes, we found that CREB dephosphorylation causes PGC1 and BDNF loss of functions. Our data was validated in vitro and in vivo. The negative effect of gp120 was alleviated in cells and animals in the presence of rolipram that inhibits the phosphodiesterase protein 4 (PDE4) and restores CREB phosphorylation. We concluded that HIV-gp120 protein contributes to HAND via inhibition of CREB protein function.